(untitled) (The Conference Hub, 2025)
The public-private partnership (PPP) model has emerged over the past two decades as an important tool for attracting investments and implementing strategic projects in the global economy. Global experience shows that PPPs serve to enhance economic efficiency in key sectors such as energy, transport, infrastructure, healthcare, and others. The PPP model allows financing of major capital projects by optimizing public financial resources and leveraging the expertise and innovations of the private sector.